2012
DOI: 10.1111/j.1752-4571.2011.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic monitoring and complex population dynamics: insights from a 12‐year study of the Rio Grande silvery minnow

Abstract: The endangered Rio Grande silvery minnow persists as a remnant population in a highly fragmented and regulated arid-land river system. The species is subject to dramatic annual fluctuations in density. Since 2003, the wild population has been supplemented by hatchery-reared fish. We report on a 12-year (1999–2010) monitoring study of genetic diversity and effective population size (Ne) of wild and hatchery stocks. Our goals were to evaluate how genetic metrics responded to changes in wild fish density and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 77 publications
(139 reference statements)
3
71
0
Order By: Relevance
“…This section is fragmented by three diversion dams (maximum fragment length 90 rkm) that are impassable in the upstream direction. In most years since 2003, the wild populations of Rio Grande silvery minnow have been augmented, primarily with fish reared from captive broodstock or from wild‐caught eggs hatched and reared in captivity before transfer to the wild (Osborne, Carson & Turner, ). Genetic monitoring of wild and captive stocks occurred in 1987 and annually since 1999.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section is fragmented by three diversion dams (maximum fragment length 90 rkm) that are impassable in the upstream direction. In most years since 2003, the wild populations of Rio Grande silvery minnow have been augmented, primarily with fish reared from captive broodstock or from wild‐caught eggs hatched and reared in captivity before transfer to the wild (Osborne, Carson & Turner, ). Genetic monitoring of wild and captive stocks occurred in 1987 and annually since 1999.…”
Section: Resultsmentioning
confidence: 99%
“… Estimates of N e are small relative to abundances of the adult population (Aló & Turner, ; Osborne et al., ). Normally, N e is smaller than N c , the census population size (Palstra & Ruzzante, ), but this is exaggerated in Rio Grande silvery minnow in which some estimates of variance effective population size ( N eV < N e estimated from temporal variation in N c ) are <100 at times when N c is 10,000s.…”
Section: Resultsmentioning
confidence: 99%
“…Data from neutral loci have also shown that over the species' current range, there is no population structure due to the drifting nature of Rio Grande silvery minnow eggs (Osborne et al . ). However, these studies do not allow for specific predictions about whether species harbour genetic diversity needed to respond to immunological stressors.…”
Section: Introductionmentioning
confidence: 97%
“…Since 2002, the Rio Grande silvery minnow population has been supported to varying degrees by augmentation (Osborne et al . ) to prevent extinction. We have tracked neutral genetic diversity in Rio Grande silvery minnow (Alò & Turner ; Turner et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation